Nonallergic Rhinitis: Diagnosis and Management. (2nd September 2014) - Krouse, John H.; Joe, Stephanie; Luong, Amber U.; Reisacher, William R.; Toskala, Elina M.
Abstract : Program Description: Patients with nonallergic rhinitis (NAR) are commonly seen in an otolaryngologist's practice. These patients may have no allergic triggers, may be negative to routine allergy testing, and are therefore diagnosed with NAR. Recent workgroups both in the United States and internationally have attempted to better classify the pathophysiology and phenotype of patients with NAR, with the goal of facilitating more accurate diagnosis and improved treatment. This panel will review, through brief didactic discussions and case presentations, recent knowledge and current understanding of NAR and will highlight methods to improve the management of these frequently challenging patients. Educational Objectives: (1) Discuss the various pathophysiologies and presentations that are grouped under the diagnostic category of nonallergic rhinitis. (2) Review important elements of the diagnostic workup in evaluating the patient with nonallergic rhinitis. (3) Implement treatment strategies for patients diagnosed with nonallergic rhinitis.